Algorithm of 3D Dirichlet problem solution for convection-diffusion equation - Dudykevych, A. T.; Kardash, A. I.; Levytska, S. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Spatial equation of convection-diffusion with variable coefficients by mesh method at 19-point pattern is reduced to the system of finite difference equations and is solved applying the upper-relaxation method by points and lines.